Pengaruh Pemberian Glukosa Oral 40% Terhadap Respon Nyeri Pada Bayi Yang Dilakukan Imunisasi Pentavalen Di Puskesmas Baki Sukoharjo - Clara, Lita Andes, Sulastri , S.Kp, M.Kes, Endang Zulaicha Susilaningsih , S.Kp, M.Kep (2015)
Immunization is one of minor invasive procedures which could make pain to the infant. The pain feeling, will cause uncomfortable for the infant. One of pain's management of non pharmacology is by giving oral glucose liquid. Analgesia glucose effect can happen because the effect of released beta endorphin, which could decrease pain's signal transmission to central nervous system. The Purpose of this research is to know the effect from giving oral glucose 40% for pain respon to infant who get Pentavalen immunization. This research method is use quash experiment with after only nonequivalent control group design. The Sampling technique in this research is use consecutive sampling method. Sample in this research amount 40 respondents, devided to be two groups, that was 20 persons for intervention group and 20 persons for control group. Distribution of intervention of oral glucose 40% is giving first from 2 minutes before immunization procedures and than measuring pain responses with behavior scale FLACC during 5 minutes after injection with first scaling during injection, and 3 minutes after injection and than 5 minutes after injection. The Data analysis technique for knowing different pain respon is use Mann-Whitney Test.. Result from the statistics, pain responses analysis during injection obtain p value > 0,05 was 0,235 and pain responses analysis in third minutes and fifth minutes had different pain responses, that's mean between intervention group and control group had value p = 0,001 (p value <0,05. So can conclude that give oral glucose 40% have occur effect in pain responses to infant who got Pentavalen Immunization.